DYSTROPHIC-DESTRUCTIVE PROCESSES IN THE PROSTATE GLAND ON THE THIRD DAY AFTER THE ACTION OF COLD FACTOR - Попадинець, О.Г. (World of Medicine and Biology, 2014)
Our work presents the results of a comprehensive study of the morphofunctional condition of the structural components of the prostate gland on the third day after exposure to cold factor, performed in the experiment on 20 mature white outbred male rats. In all lobes of the prostate gland (ventral, dorsal, coagulation glands) the sharply expressed dystrophic-destructive changes of blood vessels, glandular epithelium, connective tissue framework were found.
Keywords: prostate gland; mature rats; general deep hypothermia